Makassar Strait Thrust - Mamuju Segment (MSTM) Perspective on Radioactive Mineral Exploration: A Case Study in Rantedoda, Mamuju - Ciputra, Roni Cahya; Pratiwi, Fadiah; Putra, Aldo Febriansyah; Syaeful, Heri; Indrastomo, Frederikus Dian; Adimedha, Tyto Baskara; Rachael, Yoshi; Sukadana, I Gde (Geological Agency, 2025)
The Makassar Strait Thrust – Mamuju Segment (MSTM) is a key structural feature influencing uranium (U), thorium (Th), and rare earth element (REE) mineralization in Mamuju, West Sulawesi. This study explores the relationship between tectonic deformation, weathering processes, and mineralization, focusing on the Rantedoda sector. Integrated geomorphic, geological, radiometric, petrographic, and geochemical analyses reveal that MSTM faults act as conduits for hydrothermal fluids, promoting mineral mobilization, alteration, and enrichment in fault zones. MSTM produced curved NW ̶ SE to N ̶ S thrusts torn by NE ̶ SW right-lateral strike-slip faults in the studied area. Radiometric data highlight anisotropic distributions of U, Th, and dose rates aligned with NE ̶ SW and NW ̶ SE fault trends. Geochemical indices demonstrate that weathering is critical for REE and Th enrichment, as high eTh and low K values indicate. Moreover, fault-facilitated hydrothermal clay alteration supports U adsorption, as noted by high values of all radiometric parameters in the area near a fault. These findings establish the critical role of fault systems in controlling mineralization processes, providing a framework for targeted exploration strategies in tectonically complex terrains of the Mamuju area.